Ascribing Sentience: Evidential and Ethical Considerations in Policymaking - James William Yeates (Animals, 2022)
Deciding which animals are sentient is an important precursor for decisions about the application of animal welfare legislation, and the wider assessment of the impacts of policies on animal suffering. We ascribe sentience in order to inform decisions about how animals should be treated, and how their treatment should be regulated. This ascription is both an ethical and an evidential process, and what evidence to use and require are ethical questions. Policymakers, therefore, cannot simply rely on scientific evidence in an ethically neutral way, but must be conscious of the ethical assumptions and positions underlying the process of ascription and its application in policy and law. As such, ethical principles that apply to policymaking apply to the ascription of sentience. This paper considers the implications of the Nolan principles for public service on the ascription of animals.